Seasonal variation in mosquito abundance and environmental predictors in semi-pastoral southern Kenya: implications for endemic Rift Valley fever - Gerken, Keli N.; Olubowa, Richard R.; Chiuya, Tatenda; Korir, Max; Fèvre, Eric M.; Stringer, A.; Morse, A.; Baylis, M. (BioMed Central, 2026)
Background: Ecological variables that vary across time and space shape mosquito populations, creating microenvironments that can become disease transmission hotspots. Rift Valley fever virus (RVFV), a priority zoonotic arbovirus, thrives in diverse conditions and has been detected in over 50 mosquito species. This diversity complicates efforts to identify the key vectors involved in transmission and highlights the need to understand how environmental conditions shape mosquito abundance in high-risk landscapes.